Hakikat, Nilai-Nilai Dan Strategi Pembentukan Karakter (Akhlak) Dalam Islam - Ainna Khoiron Nawali (TA'LIM : Jurnal Studi Pendidikan Islam, 2018)
This paper will discuss the nature, values ​​and strategy formation of character in Islam. See the environment around us, especially urban areas many children aged students do not have good character in their daily life, even every behavior there are no values ​​in accordance with the teachings of Islam. Like ditching school, fights and others, even educated people also often has a bad character, such as corruption, collusion and nepotism (KKN). Everyone has the nature of the different characters, to the need for specific strategies so that everyone has the character that corresponds to the values ​​and norms of society and of course in accordance with the teachings of Islam.